The changing role of IP. A case study of open innovation in automotive - Dahl, Erik (My University, 2020)
Firms are turning the focus from production equipment and machines to management of information and knowledge, with the entrance into the fourth industrial revolution. This evolution poses new types of challenges, but also provides opportunities. In combination with this paradigm shift, many industries are experiencing converging technologies with ICT companies entering into new application areas. This has been especially evident in the automotive industry. One strategy is to collaborate with these new actors through open innovation. However, the capability to manage and trade knowledge is less established at the OEMs. That is why this capability needs to be developed. The IP function is already used to work with intangible assets and might play a central part in this transformation. This study aimed to understand the role of IP management in projects where an OEM incorporates an innovative technology by collaborating with an external actor. This was done through a multiple case study of two collaboration projects at Polestar, with data from 12 interviews and project documents. The two case studies were very different, which highlights the need to adapt the IP management to the specific conditions of each project. However, the result showed that one of the main objectives of IP management was to assemble the parties resources and construct a framework that allocates the project results. This role is explored in the literature, while the results from this study provide an additional perspective on how IP management can be adapted to fast-paced environments and start-ups with limited time and resources. One of the main findings was that a cross-functional team consisting of IP, business and technology expertise would manage any IP at the time it is created in the project. By agreeing on the basic principles for allocating IP results, at the start of the project, some elements of the IP management can be pushed to the future. This setup allocates the team’s time and resources to the projects generating the most IP.
Keywords: IP management; Open innovation; Collaboration; R&D; Patent; Automotive